The Distribution and Abundance of Terrestrial Vertebrates of the James and Hudson Bay Regions of Québec - Bider, J. (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1976)
From an increasing number of surveys conducted in northern Québec interior at all times of the year, a view of animal resources and their distribution is crystallizing. In retrospect the distribution of animals seems for the most part related to the distribution of nutrient rich areas much like the distribution of animals in the desert relates to water. About 50% of all summer animal activity takes place on vast areas of poor habitat which comprises approximately 90% of the region. The small concentrations of nutrients from these regions where they are captured and transformed through food chains to a variety of carnivores such as those found at all major rapids. In the rich Tyrrell Sea the most salient factors which affect the populations seem to be the drainage of the soil and the turbidity of the water. The reduction of forest crown cover seems to affect the changes in species composition rather than the function of animals. In reviewing all the above factors and the known ranges of the animals it seems that western Nouveau-Québec can be divided into six zoogeographical entities, three of which are affected by the rich marine deposits of the Tyrrell Sea, topography and climate, the three others by the extremely poor glacial soils, topography and climate.